Globalizing Local Content as A New Concept In Planning Education: Experience in Developing Double Master Degree Program Between University of Groningen, The Netherlands and Institut Teknologi Bandung, Indonesia - Haryo Winarso (The Institute for Research and Community Services, Institut Teknologi Bandung, 2007)
In the past, developing curricula for planning education in developing countries could mean asking for assistance from the western universities to set up a degree program, using western planning tools to be put into social and cultural specific of the developing countries. Most of such collaboration would ignore the potency of knowing the two different worlds. Those view is no longer appropriate as globalisation in planning discipline is inescapable, dualistic views on the planning in rich and poor countries has to be seen as a strong point for planning education especially because education itself is now globalising. The trend for global education is visible, collaboration between developed and developing countries universities are everywhere not only for the financial reasons but also because economic, environment, social and cultural development are now cross border, and this often involving conflict and a lliance across ethno national. Within the above framework, this paper discusses the development of curricula of the Department of City and Regional Planning of the Institute Teknologi Bandung, since the department was set up with the help of the United Nation in 1959; the development of Master degree programme with the assistance of the DevelopmentPlanning Unit, University College London; and the development of Double Master Degree Programme in collaboration with the Faculty of Spatial Sciences, RUG. It is argued that the curricula has been developed in response to the changing planning context in national as well as international level and that planning education has to be able to enrich students not only with the analytical, tech nical and socio political knowledge of local content of developing countries but also the content of developed countries as these two knowledge will enhance understanding of global development problems.